A facile crush-and-sieve treatment for recycling end-of-life photovoltaics. (1st February 2023) - Sim, Ying; Tay, Yeow Boon; Pham, Huu Khue; Mathews, Nripan
Graphical abstract: With increased photovoltaic installations, it is essential to explore more efficient recycling alternatives. This study for the first time demonstrates the inhibition by polymeric encapsulation layers on the metal dissolution and highlights the advantages of a simple crush-and-sieve procedure in size-selective separation to obtain polymer-retained fractions and silver-enriched fraction without the use of burning processes. Highlights: Deployment of photovoltaics (PV) has increased tremendously over the past decades. Conventional PV recycling uses thermal treatment to free PV cells for metal recovery. Thermal treatment emits harmful and noxious by-products. Crush and sieve results in silver-rich fraction for higher efficient recycling. Abstract: The shift towards renewable energy mix has resulted in an exponential growth of the photovoltaic (PV) industry over the past few decades. Parallelly, new recycling technology developments are required to address the incoming volume of waste as they gradually approach their end-of-life (EoL) to realize the concept of a circular economy. Typical recycling processes involve high-temperature burning for separation and release of the PV cells for metal recovery processes. However, this thermal process generates gaseous by-products that cause serious health and environmental issues. Eschewing the need for burning, we demonstrate a simple crush-and-sieve methodology to strategically aids the separation of polymeric and metallic contents. The proposed approach showcased the efficient size-selective separation and generated polymer- and metal-rich fractions. More than 90 % of the total polymer present within the studied wastes was found to be retained in larger sized-particle fractions (F1 and F2). Metal content analysis highlighted the enrichment of highly valuable silver into the smallest sized-particle fraction (F4), accounting up to 70 % and 80 % of total silver present respectively for EVAc and MP. The benefits ripe through this simple crush-and-sieve method offers an attractive pathway for PV recycling process to obtain metal-rich fractions and allow focused recovery of valuable materials through an environmentally friendlier manner.